Original paperEFFECT OF MUSIC ON ANAEROBIC EXERCISE PERFORMANCE - Atan, T. (Biology of Sport, 2013)
For years, mostly the effects of music on cardiorespiratory exercise performance have been studied, but a few studies have examined the effect of music on anaerobic exercise. The purpose of this study was to assess the effect of listening to music and its rhythm on anaerobic exercise: on power output, heart rate and the concentration of blood lactate. 28 male subjects were required to visit the laboratory on 6 occasions, each separated by 48 hours. Firstly, each subject performed the Running-based Anaerobic Sprint Test (RAST) under 3 conditions on separate days: while listening to “slow rhythm music”, “fast rhythm music” or “no music”. 48 hours after the subjects completed RAST under 3 conditions, Wingate Anaerobic Power (WAN) tests were performed under 3 music conditions. The order of the 3 conditions (slow music, fast music and no music) was selected randomly to prevent an order effect. Results showed no significant differences between 3 conditions in anaerobic power assessments, heart rate or blood lactate (p>0.05). On the basis of these results it can be said that music cannot improve anaerobic performance. The type of music had no impact on power outputs during RAST and WAN exercise. As a conclusion, listening to music and its rhythm cannot enhance anaerobic performance and cannot change the physiological response to supramaximal exercise.